(Meth)acrylic pressure-sensitive adhesive film and display component including the same

By developing an adhesive composition containing a (meth)acrylic pressure-sensitive adhesive film that maintains excellent viscoelasticity and recovery over a wide temperature range, the adhesive film in the prior art has been solved. The problem of insufficient viscoelasticity and recovery in a wide temperature range enables efficient bonding and recovery performance.

CN115124945BActive Publication Date: 2025-02-14SAMSUNG SDI CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210741771.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2015-02-17
Filing Date
2015-10-30
Publication Date
2025-02-14
Estimated Expiration
2035-10-30

AI Technical Summary

Technical Problem

Existing transparent adhesive films are difficult to maintain excellent viscoelasticity and recovery over a wide temperature range, especially in applications with flexible optical displays.

Method used

Developed an adhesive composition consisting of a (meth)acrylic pressure sensitive adhesive film comprising a monomer mixture forming a (meth)acrylic copolymer containing a comonomer which is homopolymerized The substance has a glass transition temperature of -150°C to 0°C, and organic particles are added to the binder composition to improve viscoelasticity.

Benefits of technology

It achieves excellent viscoelasticity and recovery in a wide temperature range of -20°C to 80°C, improves the energy storage modulus and T peel strength of the adhesive film, reduces the bubble generation area, and maintains high transparency. luminosity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115124945B_ABST
    Figure CN115124945B_ABST
Patent Text Reader

Abstract

The present invention discloses a (meth)acrylic pressure-sensitive adhesive film and a display component comprising the same. The (meth)acrylic pressure-sensitive adhesive film has an average slope of 9.9 to 0, measured in a storage modulus to temperature relationship diagram in the range of 20°C to 80°C, wherein the x-axis represents temperature and the y-axis represents storage modulus. The (meth)acrylic pressure-sensitive adhesive film has a storage modulus at 20°C of 10 kPa to 1,000 kPa. The (meth)acrylic pressure-sensitive adhesive film is formed by an adhesive composition including a monomer mixture forming a (meth)acrylic copolymer, the monomer mixture including a comonomer, and the homopolymer of the comonomer has a glass transition temperature of 150°C to 0°C. The (meth)acrylic pressure-sensitive adhesive film can maintain viscoelasticity in a wide temperature range and also exhibits excellent recoverability.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention is a divisional application of the invention patent application with application number 201510729509.4 filed on October 30, 2015 and invention name “Adhesive film and display component comprising adhesive film”.

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims priority to and the benefit of Korean Patent Application Nos. 10-2014-0150799, filed on November 1, 2014, 10-2014-0151571, filed on November 3, 2014, 10-2014-0156462, filed on November 11, 2014, and 10-2015-0024448, filed on February 17, 2015, filed in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference. Technical Field

[0004] The present invention relates to an adhesive composition, a (meth)acrylic pressure-sensitive adhesive film formed of the adhesive composition, and a display component including the (meth)acrylic pressure-sensitive adhesive film. Background Art

[0005] The transparent adhesive film is used as an adhesive film for interlayer bonding of stacked parts in optical displays or in connection of touch screens of mobile phones.

[0006] Specifically, the capacitive touch panel in the optical display is attached to a window or film via an adhesive film and has its characteristics by sensing the capacitance change of the window or film. The adhesive film in the touch panel is stacked between the window glass and the TSP sensor glass.

[0007] The transparent adhesive film has the advantage of improving screen clarity compared to existing double-sided tapes, and exhibits good adhesion while acting like glass, transmitting 97% or more of light. The transparent adhesive film can be used for tablet computers, TVs, etc., including medium-sized or large-sized display screens and mobile phones.

[0008] Recently, as the environment in which optical displays are used, stored, and / or manufactured becomes harsher and interest in flexible optical displays is increasing, etc., transparent adhesive films require various properties. In particular, for the application of flexible displays, a transparent adhesive film that maintains viscoelasticity in a wide temperature range and also exhibits excellent recoverability is required.

[0009] One example of the prior art is disclosed in Korean Patent Publication No. 2007-0055363A. Summary of the invention

[0010] One aspect of the present invention is to provide an adhesive composition, a (meth)acrylic pressure-sensitive adhesive film formed of the adhesive composition, and a display component including the (meth)acrylic pressure-sensitive adhesive film, wherein the adhesive composition exhibits excellent characteristics in terms of reliability, recoverability, light transmittance and adhesive force under harsh conditions while maintaining viscoelasticity in a wide temperature range.

[0011] According to one aspect of the present invention, the (meth)acrylic pressure-sensitive adhesive film has an average slope of -9.9 to 0, measured in a storage modulus versus temperature plot in the range of -20°C to 80°C, wherein the x-axis represents temperature (°C) and the y-axis represents storage modulus (kPa). The (meth)acrylic pressure-sensitive adhesive film has a storage modulus at -20°C of 10 kPa to 1,000 kPa. The (meth)acrylic pressure-sensitive adhesive film is formed from an adhesive composition, the adhesive composition comprising a monomer mixture forming a (meth)acrylic copolymer, the monomer mixture comprising a comonomer, a homopolymer of the comonomer having a glass transition temperature of -150°C to 0°C.

[0012] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have a storage modulus at -20°C of 10 kPa to 500 kPa.

[0013] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have a storage modulus at -20°C of 20 kPa to 200 kPa.

[0014] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have a storage modulus at -20°C of 50 kPa to 200 kPa.

[0015] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have a storage modulus at 80° C. of 10 kPa to 1,000 kPa.

[0016] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have a storage modulus at 80° C. of 10 kPa to 500 kPa.

[0017] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have a storage modulus at 80° C. of 10 kPa to 100 kPa.

[0018] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have a storage modulus at 80° C. of 10 kPa to 30 kPa.

[0019] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have an average slope of -6 to 0.

[0020] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have an average slope of −5 to 0.

[0021] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have an average slope of −4 to 0.

[0022] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have an average slope of -3 to 0.

[0023] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have an average slope of −1.2 to 0.

[0024] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have an average slope of −1.0 to 0.

[0025] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have an average slope of −0.5 to 0.

[0026] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have a T-peel strength of 400 gf / in (gf / in) to 4,000 gf / in measured at 25° C. with respect to a corona-treated polyethylene terephthalate (PET) film.

[0027] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have a T-peel strength of 200 to 2,000 g-f / inch, measured at 60° C. with respect to a corona-treated polyethylene terephthalate (PET) film.

[0028] In one embodiment, the monomer mixture may further include a hydroxyl-containing (meth)acrylate.

[0029] In one embodiment, the adhesive composition may further include organic particles.

[0030] In one embodiment, the organic particles may have an average particle size of 10 nanometers to 400 nanometers.

[0031] In one embodiment, the organic particles may be present in an amount of 0.1 parts by weight to 15 parts by weight based on 100 parts by weight of the monomer mixture forming the (meth)acrylic copolymer.

[0032] In one embodiment, the refractive index difference between the organic particles and the monomer mixture may be 0.5 or less.

[0033] In one embodiment, the monomer mixture may include 5 to 40 wt % of the hydroxyl-containing (meth)acrylate monomer and 60 to 95 wt % of the comonomer, based on the total amount of the monomer mixture.

[0034] In one embodiment, the comonomer can be selected from the group consisting of (meth) acrylate monomers, ethylene oxide-containing monomers, propylene oxide-containing monomers, amine-containing monomers, amide-containing monomers, alkoxy-containing monomers, phosphoric acid-containing monomers, sulfonic acid-containing monomers, phenyl-containing monomers, silane-containing monomers, and combinations thereof.

[0035] In one embodiment, the monomer mixture may further include a carboxyl group-containing monomer.

[0036] In one embodiment, the adhesive composition may further include at least one of an initiator and a cross-linking agent.

[0037] In one embodiment, the adhesive composition may further include a silane coupling agent.

[0038] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film having a thickness of 100 micrometers may have a haze of 5% or less.

[0039] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film having a thickness of 100 micrometers may have a haze of 5% or less, as measured after the (meth)acrylic pressure-sensitive adhesive film undergoes 200% stretching.

[0040] In one embodiment, a (meth)acrylic pressure-sensitive adhesive film having a thickness of 100 micrometers may have a recovery rate of 30% to 98%, as represented by Equation 3:

[0041] [Equation 3]

[0042] Recovery rate (%) = (1-(X f / X 0 ))×100

[0043] Where X 0 is the initial thickness of the (meth)acrylic pressure-sensitive adhesive film, and X f It is the length of the (meth)acrylic pressure-sensitive adhesive film increased after a test piece including a first end of a first polyethylene terephthalate film attached to the (meth)acrylic pressure-sensitive adhesive film, a second end of the (meth)acrylic pressure-sensitive adhesive film attached to a second polyethylene terephthalate film is pulled at a rate of 300 mm / min to a length 10 times the initial thickness of the (meth)acrylic pressure-sensitive adhesive film, maintained at the position for 10 seconds, and then recovered at the same rate as the stretching rate, and subsequently a force of 0 kPa is applied to the (meth)acrylic pressure-sensitive adhesive film.

[0044] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may have a bubble generation area of ​​0%, as measured by folding a (meth)acrylic pressure-sensitive adhesive film sample including a first polyethylene terephthalate film having a thickness of 50 μm stacked on one surface of the (meth)acrylic pressure-sensitive adhesive film and a second polyethylene terephthalate film having a thickness of 100 μm stacked on a second surface of the (meth)acrylic pressure-sensitive adhesive film in half, then placing the (meth)acrylic pressure-sensitive adhesive film sample between parallel frames having a gap of 1 cm, and then subjecting the (meth)acrylic pressure-sensitive adhesive film sample to aging for 24 hours under the conditions of 70° C. and 93% RH.

[0045] In one embodiment, the (meth)acrylic pressure-sensitive adhesive film may be an adhesive film cured by ultraviolet light irradiation.

[0046] According to another aspect of the present invention, a display member may include an optical film and a (meth)acrylic pressure-sensitive adhesive film attached to one or both surfaces of the optical film. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 is a cross-sectional view of a display component according to an embodiment of the present invention.

[0048] 2( a ) and 2 ( b ) are conceptual diagrams of samples for measuring T-peel strength.

[0049] 3( a ) and 3 ( b ) are a cross-sectional view and a plan view of a sample used for measuring the recovery rate. DETAILED DESCRIPTION

[0050] As used herein, the term "(meth)acrylate" may refer to acrylate and / or methacrylate.

[0051] As used herein, the term "copolymer" may include oligomers, polymers, and resins.

[0052] As used herein, the term "comonomer" refers to a monomer polymerized with the hydroxyl-containing (meth)acrylate, and may be, but is not limited to, any monomer as long as the monomer can be polymerized with the hydroxyl-containing (meth)acrylate.

[0053] As used herein, the term "glass transition temperature of a comonomer or monomer" can be measured, for example, using DSC Q20 (TA Instrument Inc.) to measure the glass transition temperature of a homopolymer of each monomer. Specifically, the homopolymer of each monomer is heated to 160° C. at a rate of 20° C. / min, then the homopolymer is slowly cooled to maintain an equilibrium state at 50° C., and then heated to 160° C. at a rate of 10° C. / min to obtain data of an endothermic transition curve. The inflection point of the endothermic transition curve is the glass transition temperature.

[0054] As used herein, the term "average slope" refers to the average slope in the range of -20°C to 80°C in a graph depicting the temperature-dependent storage modulus distribution of an adhesive film, wherein the x-axis represents temperature (°C) and the y-axis represents storage modulus (kPa), and is calculated by Equation 1:

[0055] [Equation 1]

[0056] Average slope=(Mo(80℃)-Mo(-20℃)) / (80-(-20))

[0057] (wherein Mo(80°C) is the storage modulus at 80°C, and Mo(-20°C) is the storage modulus at 20°C).

[0058] As used herein, the term "T-peel strength with respect to a corona-treated polyethylene terephthalate (PET) film" refers to a value measured by the following procedures i) to v).

[0059] i) coating the adhesive composition onto a polyethylene terephthalate (PET) release film and then heating the film under 2000 mJ / cm2. 2 ) was irradiated with UV light at a dose of , thereby producing a 100 μm thick adhesive sheet of the adhesive film and the PET film.

[0060] ii) A PET film having a size of 150 mm×about 25 mm×about 75 μm (length×width×thickness) was prepared and subjected to corona treatment twice under corona discharge at a dose of 78 (total dose: 156) using a corona treatment device.

[0061] iii) An adhesive film 300 sample having a size of 100 mm x about 25 mm x about 100 μm (length x width x thickness) is obtained from the adhesive sheet, and then the corona-treated surface of the PET film 310 is laminated to both surfaces of the adhesive film 300 sample, thereby preparing a sample as shown in FIG. 2( a).

[0062] iv) The sample was autoclaved at 3.5 bar and 50° C. for 1,000 seconds and fixed to a TA.XT_Plus texture analyzer (Stable Micro Systems Co., Ltd.).

[0063] v) In a TA.XT_Plus texture analyzer, one side of the PET film 310 was kept fixed and the other side of the PET film 310 was pulled at a rate of 50 mm / min, thereby measuring the T-peel strength (see FIG. 2( b )).

[0064] As used herein, the term “T-peel strength with respect to a polyethylene terephthalate (PET) film not subjected to corona treatment (hereinafter referred to as non-corona PET)” refers to a value measured in the same manner as the method for measuring the T-peel strength with respect to a polyethylene terephthalate (PET) film subjected to corona treatment, but wherein the procedure ii) of subjecting the PET film to corona treatment is omitted.

[0065] Herein, the "recovery rate" can be measured by the following procedure: when both ends of a polyethylene terephthalate (PET) film 310 (thickness: 75 μm) each having a size of 50 mm×about 20 mm (length×width) are defined as a first end and a second end, respectively, a sample is prepared as follows: the ends of the two PET films 310 are bonded to each other in the order of the first end of the first PET film 310 / adhesive film 300 / second end of the second PET film 310 via an adhesive film 300 having a size of 20 mm×about 20 mm (length×width), and the sample has a contact area (adhesive film bonding portion 302) between each PET film 310 and the adhesive film 300 of 20 mm×about 20 mm (length×width) (see FIG. 3(a) and FIG. 3(b)). Referring to FIG. 3(a), at room temperature (25°C), clamps are fixed to the non-bonded ends (clamp fixing portions 312) of the PET films 310 of the sample, respectively. Next, the jig on one side is kept fixed, and the jig on the other side is pulled at a rate of 300 mm / min to a length of 1,000% of the thickness (unit: μm) of the adhesive film 300 (the initial thickness (X 0 ) times of the pulling rate) and then maintained for 10 seconds. Next, if a force of 0 kPa is applied to the adhesive film 300 by restoring the adhesive film 300 at the same rate as the pulling rate (about 300 mm / min), the increased length of the adhesive film 300 is defined as X f (Unit: micrometer), then the recovery rate (%) is calculated by Equation 3.

[0066] [Equation 3]

[0067] Recovery rate (%) = (1-(X f / X0 ))×100

[0068] Herein, the initial thickness of the adhesive film may be in the range of 20 μm to 300 μm. The recovery rate may be measured using a TA.XT_Plus texture analyzer (Stable Microsystems Inc.). The recovery rate may be measured at 25°C to 80°C.

[0069] As used herein, the term "bubble generation area" refers to a value (%) measured through the following procedure: an adhesive film (length×width×thickness: 13 cm×about 3 cm×about 100 μm) comprising a 50 μm thick PET film stacked on one surface and a 100 μm thick PET film stacked on the other surface is folded in half toward the 50 μm thick PET film so that the length of the adhesive film is halved, and then placed between parallel frames with a gap of 1 cm. Next, the adhesive film was subjected to aging at 70° C. and 93% RH for 24 hours, and then the image was analyzed using Mac-View software (Mountech Co., Ltd.) to measure the ratio of the area occupied by bubbles to the area of ​​the adhesive film, the image being obtained by observing the adhesive film portion subjected to bubbles using an optical microscope (EX-51, Olympus Co., Ltd., magnification: 30 times).

[0070] As used herein, the term "average particle size" refers to the z-average particle size of organic particles, as measured using a Zetasizer nano-ZS (Malvern Co., Ltd.) in a water-based solvent or an organic solvent.

[0071] As used herein, the term "core-shell structure" may refer to a typical core-shell structure including a structure having several layers of core or shell, and the term "outermost layer" refers to the outermost layer among several layers.

[0072] According to one embodiment of the present invention, the adhesive film has an average slope of -9.9 to 0, as measured in the range of -20°C to 80°C in a graph depicting the temperature-dependent storage modulus distribution of the adhesive film, wherein the x-axis represents temperature (°C) and the y-axis represents storage modulus (kPa), and the storage modulus at 80°C is 10 kPa to 1,000 kPa.

[0073] Specifically, the adhesive film may have an average slope of -9.9 to 0, -9 to 0, -8 to 0, -7 to 0, -6 to 0, -5 to 0, -4 to 0, -3 to 0, -2.9 to 0, -2.8 to 0, -2.7 to 0, -2.6 to 0, -2.5 to 0, -2.4 to 0, -2.3 to 0, -2.2 to 0, -2.1 to 0, -2.0 to 0, -1.9 to 0, -1.8 to 0, -1.7 to 0, -1.6 to 0, -1.5 to 0, -1.4 to 0, -1.3 to 0, -1.2 to 0, -1.1 to 0, -1.0 to 0, -0.9 to 0, -0.8 to 0, -0.7 to 0, -0.6 to 0 or -0.5 to 0. In addition, the average slope of the adhesive film may be in the range of one of the above-mentioned values ​​to another of the above-mentioned values. For example, the average slope of the adhesive film may be -5 to 0, specifically -2 to 0. Within this range, the adhesive film can exhibit viscoelasticity and excellent recovery rate in a wide temperature range, and can be used for flexible optical parts.

[0074] The average slope refers to the average slope in the range of -20°C to 80°C in a graph depicting the temperature-dependent storage modulus distribution of the adhesive film, with the x-axis representing temperature (°C) and the y-axis representing storage modulus (kPa), and is calculated by Equation 1:

[0075] [Equation 1]

[0076] Average slope=(Mo(80℃)-Mo(-20℃)) / (80-(-20))

[0077] (wherein Mo(80°C) is the storage modulus at 80°C, and Mo(-20°C) is the storage modulus at 20°C).

[0078] In addition, the adhesive film has a storage modulus of 10 kPa to 1,000 kPa at 80° C. Specifically, the adhesive film may have a storage modulus of 10 kPa to 1,000 kPa, 10 kPa to 900 kPa, 10 kPa to 800 kPa, 10 kPa to 700 kPa, 10 kPa to 600 kPa, 10 kPa to 500 kPa, 10 kPa to 400 kPa, 10 kPa to 300 kPa, 10 kPa to 200 kPa, 10 kPa to 100 kPa, 10 kPa to 90 kPa, 10 kPa to 80 kPa, 10 kPa to 70 kPa, 10 kPa to 60 kPa, 10 kPa to 50 kPa, 10 kPa to 40 kPa, or 10 kPa to 30 kPa. In addition, the adhesive film may have a storage modulus at 80°C in the range of one of the above values ​​to another of the above values. Within this range, the adhesive film maintains viscoelasticity and good recovery rate at high temperatures. For example, the adhesive film may have a storage modulus at 80°C in the range of 10 kPa to 500 kPa, more specifically 10 kPa to 300 kPa.

[0079] The T-peel strength of the adhesive film may be 200 gf / inch, 300 gf / inch, 400 gf / inch, 500 gf / inch, 600 gf / inch, 700 gf / inch, 800 gf / inch, 900 gf / inch, 1000 gf / inch, 1100 gf / inch, 1200 gf / inch, 1300 gf / inch, 1400 gf / inch, 1500 gf / inch, 1600 gf / inch, 1700 gf / inch, 1800 gf / inch, 1000 gf / inch, 1500 gf / inch, 1900 gf / inch, 2000 gf / inch, 2100 gf / inch, 2200 gf / inch, 2300 gf / inch, 2400 gf / inch, 2500 gf / inch, 2600 gf / inch, 2700 gf / inch, 2800 gf / inch, 2900 gf / inch or 3000 gf / inch, as measured at 25°C on a polyethylene terephthalate (PET) film that is not corona treated (hereinafter referred to as a non-corona PET film). In addition, the adhesive film may have a T-peel strength ranging from one of the above-recited values ​​to another of the above-recited values, as measured at room temperature (about 25°C) on a non-corona PET film. For example, the adhesive film may have a T-peel strength of 200 gf / inch to 3,000 gf / inch, specifically 300 gf / inch to 2,500 gf / inch, more specifically 400 gf / inch to 2,000 gf / inch, as measured with respect to a non-corona PET film at 25° C. Within this range, the adhesive film exhibits excellent room temperature adhesion and reliability.

[0080] The adhesive film may have a T-peel strength of 100 gf / inch, 200 gf / inch, 300 gf / inch, 400 gf / inch, 500 gf / inch, 600 gf / inch, 700 gf / inch, 800 gf / inch, 900 gf / inch, 1000 gf / inch, 1100 gf / inch, 1200 gf / inch, 1300 gf / inch, 1400 gf / inch, 1500 gf / inch, 1600 gf / inch, 1700 gf / inch, 1800 gf / inch, 1900 gf / inch, or 2000 gf / inch, as measured at 60°C on a polyethylene terephthalate (PET) film that has not been corona treated (hereinafter referred to as a non-corona PET film). In addition, the adhesive film may have a T-peel strength ranging from one of the above-described values ​​to another of the above-described values, as measured at high temperature (60° C.) with respect to a non-corona PET film. For example, the adhesive film may have a T-peel strength of 100 gf / inch to 2,000 gf / inch, specifically 200 gf / inch to 1,500 gf / inch, more specifically 300 gf / inch to 1,000 gf / inch, as measured at 60° C. with respect to a non-corona PET film. Within this range, the adhesive film exhibits excellent high-temperature adhesion and reliability.

[0081] To improve the peel strength of the adhesive film, the surface coated with the adhesive composition may be subjected to surface treatment in advance, such as corona pre-treatment at 150 mJ / cm2. For example, the corona pre-treatment may be performed by treating the surface of the adherend (e.g., PET film) twice at 78 doses of corona discharge using a corona treatment device (Now plasma Co., Ltd.), but is not limited thereto.

[0082] The T-peel strength of the adhesive film may be 400 gf / inch, 500 gf / inch, 600 gf / inch, 700 gf / inch, 800 gf / inch, 900 gf / inch, 1000 gf / inch, 1100 gf / inch, 1200 gf / inch, 1300 gf / inch, 1400 gf / inch, 1500 gf / inch, 1600 gf / inch, 1700 gf / inch, 1800 gf / inch, 1900 gf / inch, 2000 gf / inch, 2100 gf / inch, 2200 gf / inch, 2300 gf / inch. 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, 1000 gf / inch, For example, the adhesive film may have a T-peel strength of 400 gf / inch to 4,000 gf / inch, specifically 600 gf / inch to 3,000 gf / inch, more specifically 1,000 gf / inch to 2,000 gf / inch, as measured with respect to a corona-treated PET film at 25° C. Within this range, the adhesive film exhibits excellent room temperature adhesion and reliability.

[0083] The adhesive film may have a T-peel strength of 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, or 2000 gf / inch as measured at 60°C on a corona treated polyethylene terephthalate (PET) film. In addition, the adhesive film may have a T-peel strength ranging from one of the above-described values ​​to another of the above-described values, as measured at high temperature (60° C.) with respect to a corona-treated PET film. For example, the adhesive film may have a T-peel strength of 200 gf / inch to 2,000 gf / inch, specifically 300 gf / inch to 2,000 gf / inch, more specifically 400 gf / inch to 1,500 gf / inch, as measured at 60° C. with respect to a corona-treated PET film. Within this range, the adhesive film exhibits excellent high-temperature adhesion and reliability.

[0084] A ratio of T-peel strength of the adhesive film with respect to the corona-treated PET film at 25° C. to T-peel strength of the adhesive film with respect to the non-corona PET film at 25° C. may be in a range of 2.5:1 to 5:1. Within this range, the adhesive film may have a balance between adhesion and reliability.

[0085] In one embodiment, the adhesive film may be formed of an adhesive composition, and the adhesive composition may include a hydroxyl-containing (meth)acrylic copolymer and organic particles.

[0086] Hereinafter, the adhesive composition will be described in detail.

[0087] Adhesive composition

[0088] Hydroxyl-containing (meth)acrylic acid copolymer

[0089] The hydroxyl-containing (meth)acrylic copolymer may be polymerized from a monomer mixture including a hydroxyl-containing (meth)acrylic acid ester monomer.

[0090] The hydroxyl-containing (meth)acrylate monomer may be a C-containing monomer having at least one hydroxyl group. 1 to C 20 Alkyl (meth) acrylate, C-containing 5 to C 20 Cycloalkyl (meth) acrylate or C-containing ester having at least one hydroxyl group 6to C 20 Aryl (meth)acrylates.

[0091] For example, the hydroxyl-containing (meth)acrylate monomer may include at least one of the following: 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate, but is not limited thereto. Specifically, the hydroxyl-containing (meth)acrylate monomer may be a C-containing (meth)acrylate monomer having a hydroxyl group. 1 to C 5 An alkyl (meth)acrylate monomer is used, whereby the adhesive composition can have further improved adhesiveness.

[0092] The hydroxyl group-containing (meth)acrylate monomer may be present in an amount of 5 to 40 wt %, for example 10 to 30 wt %, based on the total amount of the monomer mixture. Within this range, the adhesive film exhibits excellent adhesion and reliability.

[0093] In one embodiment, the hydroxyl-containing (meth)acrylic copolymer may be a polymer obtained by polymerizing a monomer mixture including a hydroxyl-containing (meth)acrylic acid ester monomer and a comonomer.

[0094] Specifically, the comonomer may include at least one of the following: an alkyl (meth)acrylate monomer, an ethylene oxide-containing monomer, a propylene oxide-containing monomer, an amine-containing monomer, an amide-containing monomer, an alkoxy-containing monomer, a phosphoric acid-containing monomer, a sulfonic acid-containing monomer, a phenyl-containing monomer, and a silane-containing monomer, but is not limited to these.

[0095] The alkyl (meth)acrylate monomer may contain unsubstituted C 1 to C 20 Straight chain or branched chain (meth) alkyl (meth) acrylate. For example, the (meth) alkyl ester monomer may include at least one of the following: methyl (meth) acrylate, ethyl (meth) acrylate, propyl (meth) acrylate, n-butyl (meth) acrylate, tert-butyl (meth) acrylate, isobutyl (meth) acrylate, pentyl (meth) acrylate, hexyl (meth) acrylate, heptyl (meth) acrylate, ethylhexyl (meth) acrylate, octyl (meth) acrylate, isooctyl (meth) acrylate, nonyl (meth) acrylate, decyl (meth) acrylate, lauryl (meth) acrylate, and isobornyl (meth) acrylate. Specifically, the (meth) alkyl ester monomer may be C 4 to C 8 The (meth)acrylic acid alkyl ester monomer can thereby further improve the initial adhesion of the adhesive composition.

[0096] The ethylene oxide-containing monomer may include at least one ethylene oxide group (—CH 2 CH 2 O-) (meth) acrylate monomer. For example, the ethylene oxide-containing monomer may include polyethylene oxide alkyl ether (meth) acrylate, such as polyethylene oxide monomethyl ether (meth) acrylate, polyethylene oxide monoethyl ether (meth) acrylate, polyethylene oxide monopropyl ether (meth) acrylate, polyethylene oxide monobutyl ether (meth) acrylate, polyethylene oxide monopentyl ether (meth) acrylate, polyethylene oxide dimethyl ether (meth) acrylate, polyethylene oxide diethyl ether (meth) acrylate, polyethylene oxide monoisopropyl ether (meth) acrylate, polyethylene oxide monoisobutyl ether (meth) acrylate, and polyethylene oxide monotert-butyl ether (meth) acrylate, but is not limited to these.

[0097] The propylene oxide-containing monomer may include polypropylene oxide alkyl ether (meth) acrylates, such as polypropylene oxide monomethyl ether (meth) acrylate, polypropylene oxide monoethyl ether (meth) acrylate, polypropylene oxide monopropyl ether (meth) acrylate, polypropylene oxide monobutyl ether (meth) acrylate, polypropylene oxide monopentyl ether (meth) acrylate, polypropylene oxide dimethyl ether (meth) acrylate, polypropylene oxide diethyl ether (meth) acrylate, polypropylene oxide monoisopropyl ether (meth) acrylate, polypropylene oxide monoisobutyl ether (meth) acrylate and polypropylene oxide monotert-butyl ether (meth) acrylate, but are not limited to these.

[0098] The amino group-containing monomer may include an amino group-containing (meth)acrylic acid monomer such as monomethylaminoethyl (meth)acrylate, monoethylaminoethyl (meth)acrylate, monomethylaminopropyl (meth)acrylate, monoethylaminopropyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, N-tert-butylaminoethyl (meth)acrylate, and methacryloyloxyethyltrimethylammonium (meth)acrylate, but is not limited to these.

[0099] The amide group-containing monomer may include an amide group-containing (meth)acrylic monomer such as (meth)acrylamide, N-methylacrylamide, N-methylmethacrylamide, N-hydroxymethyl (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N,N-methylenebis (meth)acrylamide and 2-hydroxyethyl acrylamide, but is not limited thereto.

[0100] The alkoxy-containing monomer may include 2-methoxyethyl (meth)acrylate, 2-methoxypropyl (meth)acrylate, 2-ethoxypropyl (meth)acrylate, 2-butoxypropyl (meth)acrylate, 2-methoxypentyl (meth)acrylate, 2-ethoxypentyl (meth)acrylate, 2-butoxyhexyl (meth)acrylate, 3-methoxypentyl (meth)acrylate, 3-ethoxypentyl (meth)acrylate and 3-butoxyhexyl (meth)acrylate, but are not limited to these.

[0101] The phosphoric acid group-containing monomer may include a phosphoric acid group-containing acrylic monomer, such as 2-methacryloyloxyethyldiphenylphosphate (meth)acrylate, trimethacryloyloxyethylphosphate (meth)acrylate, and triacryloyloxyethylphosphate (meth)acrylate, but is not limited to these.

[0102] The sulfonic acid group-containing monomer may include a sulfonic acid group-containing acrylic monomer such as sodium sulfopropyl (meth)acrylate, sodium 2-sulfoethyl (meth)acrylate, and sodium 2-acrylamido-2-methylpropane sulfonate, but is not limited thereto.

[0103] The phenyl group-containing monomer may include a phenyl group-containing acrylic vinyl monomer such as p-tert-butylphenyl (meth)acrylate and o-biphenyl (meth)acrylate, but is not limited thereto.

[0104] The silyl group-containing monomer may include a silyl group-containing vinyl monomer such as 2-acetoacetoxyethyl (meth)acrylate, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethyl)silane, vinyltriacetylsilane, and methacryloxypropyltrimethoxysilane, but is not limited thereto.

[0105] The comonomer may be present in an amount of 60 to 95 wt %, for example 70 to 90 wt %, based on the total amount of the monomer mixture. Within this range, the adhesive film exhibits excellent adhesion and reliability.

[0106] In another embodiment, the glass transition temperature (Tg) of the comonomer may be -150°C to 0°C. Herein, the glass transition temperature of the homopolymer of each measurement target monomer may be measured, for example, using DSC Q20 (TA Instrument Inc.). Specifically, the homopolymer of each monomer is heated to 160°C at a rate of 20°C / min, then the homopolymer is slowly cooled to maintain an equilibrium state at 50°C, and then heated to 160°C at a rate of 10°C / min, thereby obtaining data of an endothermic transition curve. The inflection point of the endothermic transition curve is determined to be the glass transition temperature. The comonomer having a glass transition temperature (Tg) of -150°C to 0°C may be (but is not limited to) any of the following comonomers, as long as the comonomer has a glass transition temperature (Tg) of -150°C to 0°C. Specifically, the comonomer may be a comonomer having a glass transition temperature (Tg) of -150°C to -20°C, and more specifically, a comonomer having a glass transition temperature (Tg) of -150°C to -40°C.

[0107] In another embodiment, the comonomer may include at least one of the following: an alkyl (meth)acrylate monomer, an ethylene oxide-containing monomer, a propylene oxide-containing monomer, an amine-containing monomer, an amide-containing monomer, an alkoxy-containing monomer, a phosphate-containing monomer, a sulfonic acid-containing monomer, a phenyl-containing monomer, and a silane-containing monomer, and the comonomer has a glass transition temperature (Tg) of -150°C to 0°C.

[0108] For example, the comonomer may include at least one of the following: an alkyl (meth)acrylate monomer, including methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl acrylate, dodecyl (meth)acrylate, etc.; an alkylene oxide-containing (meth)acrylate monomer, including polyethylene oxide monomethyl ether (meth)acrylate, polyethylene oxide monoethyl ether (meth)acrylate, polyethylene oxide monopropyl ether (meth)acrylate, polyethylene oxide monobutyl ether (meth)acrylate, polyethylene oxide monopentyl ether (meth)acrylate, polypropylene oxide monomethyl ether (meth)acrylate. , polypropylene oxide monoethyl ether (meth)acrylate, polypropylene oxide monopropyl ether (meth)acrylate, etc.; amino-containing (meth)acrylate monomers include monomethylaminoethyl (meth)acrylate, monoethylaminoethyl (meth)acrylate, monomethylaminopropyl (meth)acrylate, monoethylaminopropyl (meth)acrylate, etc.; alkoxy-containing (meth)acrylate monomers include 2-methoxyethyl (meth)acrylate, 2-methoxypropyl (meth)acrylate, 2-ethoxypropyl (meth)acrylate, etc.; and silyl-containing (meth)acrylate monomers include 2-acetoacetoxyethyl (meth)acrylate, vinyltrimethoxysilane, vinyltriethoxysilane, etc.

[0109] In one embodiment, the hydroxyl-containing (meth) acrylic copolymer can be a polymer of a mixture comprising a monomer mixture and organic particles, wherein the monomer mixture comprises a hydroxyl-containing (meth) acrylic ester monomer and a comonomer having a glass transition temperature (Tg) of -150°C to 0°C. In this embodiment, the comonomer having a glass transition temperature (Tg) of -150°C to 0°C can be present in an amount of 60 wt % to 95 wt %, such as 70 wt % to 90 wt %, based on the total amount of the monomer mixture. Within this range, the adhesive film exhibits excellent adhesion and reliability. Based on the total amount of the monomer mixture, the hydroxyl-containing (meth) acrylic ester monomer can be present in an amount of 5 wt % to 40 wt %, such as 10 wt % to 30 wt %. Within this range, the adhesive film has low turbidity and excellent adhesion.

[0110] In one embodiment, the monomer mixture may further include a carboxyl group-containing monomer.

[0111] The carboxyl group-containing monomer may include (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, 3-carboxypropyl (meth)acrylate, 4-carboxybutyl (meth)acrylate, itaconic acid, crotonic acid, maleic acid, fumaric acid and maleic anhydride, but are not limited thereto.

[0112] For example, the carboxyl group-containing monomer may be present in an amount of 10 wt % or less, specifically 7 wt % or less, more specifically 5 wt % or less, based on the total amount of the monomer mixture. Within this range, the adhesive film exhibits excellent adhesion and reliability.

[0113] The comonomer having a glass transition temperature (Tg) of -150 to 0°C may be present in an amount of 60 to 95 wt%, for example 70 to 90 wt%, based on the total amount of the monomer mixture. Within this range, the adhesive film exhibits excellent adhesion and reliability.

[0114] Organic particles

[0115] The adhesive composition or the adhesive film includes organic particles, whereby the adhesive composition or the adhesive film exhibits excellent low-temperature and / or room-temperature viscoelasticity and has stable high-temperature viscoelasticity due to its cross-linked structure. In one embodiment, the organic particles can form a chemical bond with the hydroxyl-containing (meth)acrylic acid copolymer.

[0116] Specifically, although the adhesive composition or the adhesive film includes organic particles, there is a specific refractive index difference between the organic particles having a specific average particle size described below and the hydroxyl group-containing (meth)acrylic copolymer, thereby maintaining excellent light transmittance.

[0117] The organic particles may have an average particle diameter of 10 nm to 400 nm, specifically 10 nm to 300 nm, and more specifically 10 nm to 200 nm. Within this range, aggregation of the organic particles may be prevented and the adhesive film may exhibit excellent light transmittance.

[0118] The refractive index difference between the organic particles and the hydroxyl-containing (meth)acrylic copolymer may be 0.5 or less, and specifically, may be in the range of 0 to 0.03, more specifically, 0 to 0.02. Within this range, the adhesive film exhibits excellent light transmittance.

[0119] The organic particles have a core-shell structure, and the core and the shell may have a glass transition temperature satisfying Equation 2.

[0120] [Equation 2]

[0121] Tg(c) <Tg(s)

[0122] (where Tg(c) is the glass transition temperature of the core (°C) and Tg(s) is the glass transition temperature of the shell (°C)).

[0123] The core may have a glass transition temperature of -150° C. to 10° C., specifically -150° C. to -5° C., more specifically -150° C. to -20° C. Within this range, the adhesive film may achieve a desired storage modulus at low temperatures (about -20° C.) and exhibit excellent low temperature and / or room temperature viscoelasticity.

[0124] Specifically, the core may include at least one of the (meth) acrylic acid polyalkyl esters having a glass transition temperature as described above. For example, the core may include at least one of the following: polymethyl acrylate, polyethyl acrylate, polypropyl acrylate, polybutyl acrylate, polyisopropyl acrylate, polyhexyl acrylate, polyhexyl methacrylate, polyethylhexyl acrylate, and polyethylhexyl methacrylate, but is not limited to these. Specifically, the core may include at least one of polybutyl acrylate and polyethylhexyl acrylate.

[0125] The shell may have a glass transition temperature of 15 to 150° C., for example 35 to 150° C., or more preferably 50 to 140° C. Within this range, the organic particles may exhibit excellent dispersibility in the hydroxyl-containing (meth)acrylic copolymer.

[0126] Specifically, the shell may include a (meth) acrylic acid polyalkyl ester having a glass transition temperature as described above. For example, the shell may include at least one of the following: polymethylmethacrylate (PMMA), polyethylmethacrylate, polypropylmethacrylate, polybutylmethacrylate, polyisopropylmethacrylate, polyisobutylmethacrylate, and polycyclohexylmethacrylate, but is not limited thereto. Specifically, the shell may include polymethylmethacrylate.

[0127] In another embodiment, the shell may include two or more layers, and the outermost layer of the organic particle may include at least one of the (meth) acrylic acid polyalkyl esters having a glass transition temperature of 15° C. to 150° C. Specifically, the core may include at least one of the (meth) acrylic acid polyalkyl esters having a glass transition temperature of -150° C. to 10° C., and may also include at least one of the (meth) acrylic acid polyalkyl esters having no restrictions on the glass transition temperature while allowing the glass transition temperature of the entire core to meet -150° C. to 10° C., but is not limited to these. In addition, the shell may include at least one of the (meth) acrylic acid polyalkyl esters having a glass transition temperature of 15° C. to 150° C., and may also include at least one of the (meth) acrylic acid polyalkyl esters having no restrictions on the glass transition temperature while allowing the glass transition temperature of the entire shell to meet 15° C. to 150° C., but is not limited to these.

[0128] The shell may be present in the organic particles in an amount of 1 wt % to 70 wt %, specifically 5 wt % to 60 wt %, more specifically 10 wt % to 50 wt %. Within this range, the adhesive film maintains viscoelasticity in a wide temperature range and exhibits excellent recovery rate.

[0129] In one embodiment, the organic particles included in the adhesive composition may be used in a state of being polymerized with a monomer mixture in the preparation of a hydroxyl-containing (meth)acrylic copolymer. In this case, the organic particles may be used in a state of being included in the hydroxyl-containing (meth)acrylic copolymer.

[0130] In another embodiment, the adhesive composition may include: a hydroxyl-containing (meth)acrylic copolymer; and organic particles. In this case, the organic particles may be included in the adhesive composition separately from the hydroxyl-containing (meth)acrylic copolymer.

[0131] In one embodiment, the adhesive composition may include 0.5 to 15 parts by weight, specifically 0.5 to 10 parts by weight, and more specifically 0.5 to 8 parts by weight of organic particles, based on 100 parts by weight of the monomer mixture for forming the hydroxyl-containing (meth) acrylic copolymer. Within this range, the adhesive film exhibits excellent adhesion and reliability.

[0132] In one embodiment, the adhesive composition may include: a hydroxyl-containing (meth) acrylic copolymer and organic particles, wherein the hydroxyl-containing (meth) acrylic copolymer is formed from a monomer mixture, wherein the monomer mixture includes 5 wt % to 40 wt %, such as 10 wt % to 30 wt % of a hydroxyl-containing (meth) acrylic ester monomer and 60 wt % to 95 wt %, such as 70 wt % to 90 wt % of a comonomer (e.g., a comonomer having a glass transition temperature (Tg) of -150° C. to 0° C.). Within this range, the adhesive film exhibits excellent adhesion and reliability.

[0133] In another embodiment, the adhesive composition may include: a hydroxyl-containing (meth) acrylic copolymer and organic particles, wherein the hydroxyl-containing (meth) acrylic copolymer is formed by a monomer mixture, wherein the monomer mixture includes 5 wt % to 40 wt %, such as 10 wt % to 30 wt % of a hydroxyl-containing (meth) acrylic ester monomer, 60 wt % to 95 wt %, such as 70 wt % to 90 wt % of a comonomer (e.g., a comonomer having a glass transition temperature (Tg) of -150°C to 0°C), and 10 wt % or less, specifically 7 wt % or less, more specifically 5 wt % or less of a carboxyl-containing monomer. Within this range, the adhesive film exhibits excellent adhesion and reliability.

[0134] The hydroxyl-containing (meth)acrylic copolymer may have a glass transition temperature of -150 to -13° C., for example -100 to -20° C. Within this range, the adhesive film exhibits excellent adhesion and excellent reliability in a wide temperature range while exhibiting excellent foldability.

[0135] Specifically, the hydroxyl-containing (meth) acrylic copolymer can be prepared by mixing a monomer mixture, organic particles and a free radical photopolymerization initiator, followed by solution polymerization, suspension polymerization, photopolymerization, bulk polymerization, dispersion polymerization or emulsion polymerization. Alternatively, the hydroxyl-containing (meth) acrylic copolymer can be prepared by preparing a prepolymer by partial polymerization of the monomer mixture, followed by introducing the organic particles into the prepolymer. Specifically, the emulsion polymerization can be carried out at 25° C. to 100° C. by adding a dispersant, a crosslinking agent, a monomer mixture, organic particles and an initiator. The hydroxyl-containing (meth) acrylic copolymer can be prepared by completely polymerizing the monomer mixture and the organic particles, or by partially polymerizing the monomer mixture and the organic particles, followed by completing the polymerization by adding an initiator and a crosslinking agent. The partial polymerization can be carried out by polymerizing the monomer mixture and the organic particles to a viscosity of 300 cp to 50,000 cp at 25° C.

[0136] In some embodiments, the adhesive composition may further include at least one of a cross-linking agent and an initiator.

[0137] Crosslinking agent

[0138] The crosslinking agent may be a multifunctional (meth)acrylate. Examples of the multifunctional (meth)acrylate may include bifunctional acrylates such as 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, neopentyl glycol adipate di(meth)acrylate, dicyclopentanyl di(meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified di(meth)acrylate, isocyanuric acid di(meth)acryloyloxyethyl ester, allyl di(meth)acrylate cyclohexyl, tricyclodecane dimethanol di(meth)acrylate, dimethylol dicyclopentane di(meth)acrylate, ethylene oxide-modified hexahydrophthalic acid di(meth)acrylate, neopentyl glycol-modified trimethyl propane di(meth)acrylate, adamantane di(meth)acrylate, 9,9-bis[4-(2-acryloyloxyethyl)acrylate]

[0043] The invention relates to a crosslinking agent comprising a crosslinking agent comprising a dipentaerythritol tri(meth)acrylate, a dipentaerythritol tri(meth)acrylate, a dipentaerythritol tri(meth)acrylate, a dipentaerythritol tri(meth)acrylate modified with propionic acid, a trimethylolpropane tri(meth)acrylate, a trimethylolpropane tri(meth)acrylate modified with propylene oxide, a trifunctional carbamate (meth)acrylate, a tri(meth)acryloyloxyethyl isocyanurate, etc.; a tetrafunctional acrylate, such as diglycerol tetra(meth)acrylate, a pentaerythritol tetra(meth)acrylate, etc.; a pentafunctional acrylate, such as dipentaerythritol penta(meth)acrylate, etc.; a hexafunctional acrylate, such as dipentaerythritol hexa(meth)acrylate, a dipentaerythritol hexa(meth)acrylate modified with caprolactone, and a carbamate (meth)acrylate (e.g., a reaction product of an isocyanate monomer and trimethylolpropane tri(meth)acrylate), but is not limited thereto. These crosslinking agents may be used alone or in combination. Specifically, the crosslinking agent may be a multifunctional (meth)acrylate of a polyol having 2 to 20 hydroxyl groups to provide excellent durability.

[0139] The crosslinking agent may be present in an amount of 0.01 to 10 parts by weight, specifically 0.03 to 7 parts by weight, more specifically 0.1 to 5 parts by weight, based on 100 parts by weight of the monomer mixture for forming the hydroxyl-containing (meth) acrylic copolymer. Within this range, the adhesive film exhibits excellent adhesion and improved reliability.

[0140] Initiator

[0141] The initiator may be a photopolymerization initiator or a thermal polymerization initiator.

[0142] The initiator may be the same as or different from the initiator used in the preparation of the hydroxyl-containing (meth)acrylic acid copolymer. In another embodiment, the initiator may be a thermal polymerization initiator.

[0143] The photopolymerization initiator can be any of the following initiators, as long as the initiator can achieve a second crosslinked structure by derivative polymerization of a free radical polymerizable compound during curing by light irradiation. For example, the photopolymerization initiator can include benzoin, hydroxy ketone, amino ketone, phosphine oxide photoinitiator, etc. Specifically, the photopolymerization initiator can include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin isobutyl ether, acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-N-morpholinyl-propane-1-one, 4-(2-hydroxyethoxy)phenyl-2-(hydroxy-2-propyl)ketone, benzophenone, p-phenyl Benzophenone, 4,4'-bis(diethyl)aminobenzophenone, dichlorobenzophenone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-aminoanthraquinone, 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, benzyl dimethyl ketal, acetophenone dimethyl ketal, p-dimethylaminobenzoate, oligo[2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone], and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, but are not limited thereto. These photopolymerization initiators may be used alone or in combination.

[0144] The thermal polymerization initiator may be (but is not limited to) any initiator as long as the initiator can achieve the second cross-linked structure. For example, the thermal polymerization initiator may include typical initiators such as azo compounds, peroxide compounds, and redox compounds. Examples of azo compounds may include 2,2-azobis(2-methylbutyronitrile), 2,2-azobis(isobutyronitrile), 2,2-azobis(2,4-dimethylvaleronitrile), 2,2-azobis-2-hydroxymethylpropionitrile, 2,2-methylazobis(2-methylpropionic acid dimethyl ester) and 2,2-azobis(4-methoxy-2,4-dimethylvaleronitrile), but are not limited to these. Examples of peroxide compounds may include inorganic peroxides such as potassium perchlorate, ammonium persulfate, and hydrogen peroxide; and organic peroxides such as diacyl peroxides, peroxydicarbonates, peroxyesters, tetramethylbutyl peroxyneodecanoate, bis(4-butylcyclohexyl) peroxydicarbonate, di(2-ethylhexyl) peroxycarbonate, butyl peroxyneodecanoate, dipropyl peroxydicarbonate, diisopropyl peroxydicarbonate, diethoxyethyl peroxydicarbonate, diethoxyhexyl peroxydicarbonate, hexyl peroxydicarbonate, dimethoxybutyl peroxydicarbonate, bis(3-methoxy)dioxydicarbonate, The redox compound may include, but is not limited to, a mixture of a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent. The redox compound may include, but is not limited to, a peroxide compound and a reducing agent.

[0145] The initiator may be present in an amount of 0.01 to 5 parts by weight, specifically 0.05 to 3 parts by weight, more specifically 0.1 to 1 parts by weight, based on 100 parts by weight of the monomer mixture for forming the hydroxyl-containing (meth) acrylic copolymer. Within this range, curing may be fully performed, deterioration of transmittance of the adhesive composition due to residual initiator may be prevented, generation of bubbles in the adhesive composition may be reduced, and the adhesive composition may have excellent reactivity.

[0146] In another embodiment, the adhesive composition may further include a silane coupling agent.

[0147] Silane coupling agent

[0148] The silane coupling agent may include siloxane and epoxy silane coupling agents, but is not limited thereto. The silane coupling agent may be present in an amount of 0.01 to 0.1 parts by weight, specifically 0.05 to 0.1 parts by weight, based on 100 parts by weight of the monomer mixture forming the hydroxyl-containing (meth)acrylic copolymer. Within this range, the adhesive film has improved reliability.

[0149] additive

[0150] The adhesive composition may also include typical additives, such as curing accelerators, ionic liquids, lithium salts, inorganic fillers, softeners, molecular weight regulators, antioxidants, anti-aging agents, stabilizers, adhesion-imparting resins, modified resins (polyol resins, phenol resins, acrylic resins, polyester resins, polyolefin resins, epoxy resins, epoxidized polybutadiene resins, etc.), leveling agents, defoaming agents, plasticizers, dyes, pigments (coloring pigments, body pigments, etc.), treating agents, ultraviolet blockers, fluorescent brighteners, dispersants, heat stabilizers, light stabilizers, ultraviolet absorbers, antistatic agents, coagulants, lubricants, solvents, etc.

[0151] The adhesive composition may further contain a non-curable compound.

[0152] The adhesive composition does not include a solvent and may have a viscosity of 300 centipoise (cp) to 50,000 cp at 25° C. Because the adhesive composition does not include a solvent, the adhesive composition may improve reliability by reducing bubble generation. Within this viscosity range, the adhesive composition may have excellent coatability and thickness uniformity.

[0153] adhesive film

[0154] The adhesive film can be formed from an adhesive composition as described above. Specifically, a mixture comprising a hydroxyl-containing (meth) acrylate monomer, a comonomer (e.g., a comonomer having a glass transition temperature (Tg) of -150°C to 0°C) and organic particles is polymerized to prepare a hydroxyl-containing (meth) acrylic copolymer. Alternatively, a prepolymer can be prepared by partial polymerization of the monomer mixture, and then organic particles are introduced into the prepolymer to prepare a hydroxyl-containing (meth) acrylic copolymer. The adhesive composition can be prepared as follows: an initiator and a cross-linking agent are mixed with the prepared hydroxyl-containing (meth) acrylic copolymer, followed by UV curing of the adhesive composition, thereby producing an adhesive film.

[0155] In one embodiment, the adhesive film is manufactured by mixing and polymerizing a monomer mixture, organic particles, and a photopolymerization initiator to form a hydroxyl-containing (meth) acrylic copolymer, and then adding an additional photopolymerization initiator to the polymer. The adhesive composition is coated on a release film and then cured. Curing can be performed by irradiating with a dose of 400 mJ / cm2 to 1500 mJ / cm2 at a wavelength of 300 nm to 400 nm using a low-pressure lamp in the absence of oxygen. The coating thickness of the adhesive composition can be in the range of 10 μm to 2 mm, more specifically 20 μm to 1.5 mm, but is not limited to these.

[0156] The adhesive film may be used as an OCA film, or may be formed on an optical film and thus used as an adhesive optical film. Examples of optical films may include polarizing plates. The polarizing plate includes a polarizer and a protective film formed on the polarizer, and may further include a hard coating layer, an anti-reflection layer, and the like.

[0157] In one embodiment, the adhesive film may have a storage modulus of 10 kPa to 1,000 kPa at 80° C. Within this range, the adhesive film exhibits viscoelasticity and excellent recovery rate even at high temperatures, and does not separate from an adherend even when frequently folded at high temperatures, and can prevent the adhesive film from overflowing.

[0158] The adhesive film may have a storage modulus at 25°C of 10 kPa, 20 kPa, 30 kPa, 40 kPa, 50 kPa, 60 kPa, 70 kPa, 80 kPa, 90 kPa, 100 kPa, 150 kPa, 200 kPa, 300 kPa, 400 kPa, 500 kPa, 600 kPa, 700 kPa, 800 kPa, 900 kPa or 1,000 kPa. In addition, the adhesive film may have a storage modulus at 25°C in the range of one of the above-mentioned values ​​to another of the above-mentioned values. For example, the adhesive film may have a storage modulus at 25°C of 10 kPa to 1,000 kPa, more specifically 10 kPa to 500 kPa, and more specifically 15 kPa to 300 kPa. Within this range, the adhesive film can be used for the optical substance because the adhesive film does not suffer from whitening due to its flexibility when used for a flexible device at a low temperature.

[0159] The storage modulus at -20°C of the adhesive film can be 10 kPa, 20 kPa, 30 kPa, 40 kPa, 50 kPa, 60 kPa, 70 kPa, 80 kPa, 90 kPa, 100 kPa, 150 kPa, 200 kPa, 300 kPa, 400 kPa, 500 kPa, 600 kPa, 700 kPa, 800 kPa, 900 kPa or 1,000 kPa. In addition, the storage modulus at -20°C of the adhesive film can be in the range of one of the above-mentioned numerical values ​​to another of the above-mentioned numerical values. For example, the storage modulus at -20°C of the adhesive film can be 10 kPa to 1,000 kPa, 10 kPa to 500 kPa, more specifically 20 kPa to 500 kPa. Within this range, the adhesive film exhibits viscoelasticity and excellent recovery rate at low temperatures.

[0160] In addition, the adhesive film may have a ratio of a storage modulus at 80° C. to a storage modulus at −20° C. in the range of 1:1 to 1:10, specifically 1:1 to 1:8, more specifically 1:1 to 1:5. Within this range, the adhesive film does not suffer from deterioration of adhesion between adherends in a wide temperature range (approximately −20° C. to 80° C.) and can be used for flexible optical parts.

[0161] Because the adhesive film includes organic particles, the adhesive film is flexible even at low temperatures (about -20 ° C), and the storage modulus can be kept suitable for flexible devices, showing excellent viscoelasticity at low temperatures (about -20 ° C) and / or room temperature (about 25 ° C), and showing stable viscoelasticity even at high temperatures (about 80 ° C). Because compared to the adhesive film containing only hydroxyl-containing (meth) acrylic copolymers, the adhesive film containing organic particles allows organic particles to inhibit the condensation between the substrates, so the adhesive film shows excellent wettability to the bond. Therefore, the small bubbles generated due to folding disappear as the bond unfolds or the ambient temperature changes. In addition, although the adhesive film includes organic particles, there is a specific refractive index difference between the organic particles with a specific average particle size and the hydroxyl-containing (meth) acrylic copolymer, so that the adhesive film can have excellent light transmittance. Therefore, because the adhesive film maintains viscoelasticity in a wide temperature range, the adhesive film shows excellent foldability and can be used for flexible optical components.

[0162] The adhesive film having a thickness of 100 micrometers may have a haze of 5% or less, specifically 3% or less, more specifically 2% or less, as measured after the adhesive film has been stretched 200%. Within this range, the adhesive film exhibits excellent light transmittance when used for a display.

[0163] The adhesive film having a thickness of 100 micrometers may have a recovery rate of 30% to 98%, for example 40% to 95%, or more preferably 50% to 83%, as represented by Equation 3. Within this range, the adhesive film can be used for an optical display and have a long service life.

[0164] [Equation 3]

[0165] Recovery rate (%) = (1-(X f / X 0 ))×100

[0166] (Where X 0 and X f As defined below: When the two ends of a polyethylene terephthalate (PET) film are defined as a first end and a second end, respectively, a sample is prepared by bonding the ends of the two PET films to each other in the order of a first end of the first PET film / adhesive film / second end of the second PET film via an adhesive film (length×width: 20 mm×20 mm, thickness: 75). Next, at room temperature (25° C.), clamps are respectively fixed to the unbonded ends of the PET films of the sample. Next, the clamp on one side is kept fixed, and the clamp on the other side is pulled at a rate of 300 mm / min to a length of 1,000% (initial thickness (× 100 mm) of the thickness (unit: μm) of the adhesive film. 0 ) and then maintained for 10 seconds. Then, the adhesive film is restored at the same rate as the pulling rate (about 300 mm / min), and then a force of 0 kPa is applied to the adhesive film. The increase in the length of the adhesive film is defined as X f (Unit: micrometer)).

[0167] In one embodiment, the adhesive film (thickness: 100 microns) has a recovery rate of 50% to 95%, for example 55% to 90%. Within this range, the adhesive film can prevent deformation of the adherend because the adhesive film does not suffer from deformation, even when folded hundreds or thousands of times.

[0168] In another embodiment, the adhesive film (thickness: 100 microns) may have a recovery rate of 45% to 80%, such as 49% to 75%. Within this range, the adhesive film exhibits excellent reliability because it evenly disperses the stress of the bonded body when folded.

[0169] The adhesive film (length×width×thickness: 13 cm×about 3 cm×about 100 μm) may have a bubble generation area of ​​0% as measured when the adhesive film is aged for 24 hours at 70° C. and 93% RH. Within this range, the adhesive film does not suffer from separation from the adherend even at high temperature and high humidity.

[0170] "Bubble generation area" refers to a value (%) measured by: an adhesive film (length×width×thickness: 13 cm×about 3 cm×about 100 μm) comprising a 50 μm thick PET film stacked on one surface and a 100 μm thick PET film stacked on the other surface was folded in half toward the 50 μm thick PET film so that the length of the adhesive film was halved, and then placed between parallel frames with a gap of 1 cm. Next, the adhesive film was subjected to aging at 70° C. and 93% RH for 24 hours, and then the image was analyzed using Mac-View software (Mo Teng Co.) to measure the ratio of the area occupied by bubbles to the area of ​​the adhesive film, the image being obtained by observing the adhesive film portion subjected to bubbles using an optical microscope (EX-51, Olympus Corporation, magnification: 30 times).

[0171] The adhesive film is an adhesive layer attached to one or both surfaces of an optical film and may be used to attach glass, a substrate, an electrode of a touch panel, an LCD / OLED module, a touch panel, an optical film, etc. to each other.

[0172] Specifically, the adhesive film may be used as an optically transparent adhesive film or a touch panel film.

[0173] The thickness of the adhesive film (excluding the release film) may be 1 μm to 2.0 mm, specifically 20 μm to 1.0 mm, more specifically 50 μm to 1.0 mm, but is not limited thereto. Within this range, the adhesive film may be used for optical displays.

[0174] Display Components

[0175] Another aspect of the invention relates to a display component.

[0176] The display member may include an optical film and the aforementioned adhesive film formed on one or both surfaces of the optical film.

[0177] Figure 1 is a cross-sectional view of a display component according to an embodiment of the present invention.

[0178] See also Figure 1 , the display member may include the optical film 40 and an adhesive layer or an adhesive film formed on one surface of the optical film 40 .

[0179] In one embodiment, the display member may include an optical film 40 and an adhesive layer formed on one or both surfaces of the optical film 40 .

[0180] The adhesive layer can be formed by the adhesive composition according to the present invention. Specifically, the adhesive composition prepared by mixing and polymerizing a monomer mixture for forming a hydroxyl-containing (meth) acrylic copolymer, organic particles, and a photopolymerization initiator, and then adding an additional photopolymerization initiator to the polymer is applied to the optical film 40 to form the adhesive layer.

[0181] In another embodiment, the display member may include the optical film 40 according to the present invention and an adhesive film 200 formed on one or both surfaces of the optical film 40 .

[0182] Examples of optical films may include touch panels, windows, polarizing plates, color filters, retardation films, elliptically polarizing films, reflective films, anti-reflective films, compensation films, brightness improvement films, alignment films, optical diffusion films, anti-glass break films, surface protection films, OLED device barrier layers, plastic LCD substrates, films containing indium tin oxide (ITO), films containing fluorinated tin oxide (FTO), films containing aluminum-doped zinc oxide (AZO), films containing carbon nanotubes (CNTs), films containing Ag nanowires, and transparent electrode films such as graphene, etc. The optical film can be easily manufactured by a person skilled in the art.

[0183] For example, the touch panel can be attached to a window or optical film via an adhesive film, thereby forming a display component. Alternatively, the adhesive film can be applied to a typical polarizing plate as in the art. Specifically, the display component can include a capacitive mobile phone as an optical display.

[0184] In one embodiment, the display component may be a display component in which a first adhesive film, a touch function unit, a second adhesive film, and a window film are sequentially stacked on the optical device.

[0185] The optical device may include an OLED, an LED, or a light source, and the first or second adhesive film may be an adhesive film according to the present invention. The touch function unit may be a touch panel, but is not limited thereto.

[0186] In addition, the window film may be formed of an optically transparent and flexible resin. For example, the window film may include a base layer and a hard coating layer.

[0187] The base layer may be formed of at least one of: a polyester resin such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, and polybutylene naphthalate; a polycarbonate resin; a polyimide resin; a polystyrene resin; and a poly(meth)acrylate resin such as polymethyl methacrylate.

[0188] The hard coating layer may have a pencil hardness of 6H and may be formed exclusively of a silicone resin.

[0189] In another embodiment, the display component may include: a liquid crystal panel, wherein polarizers are stacked on both surfaces of the LCD unit; a double-sided adhesive tape (DAT) that bonds functional films (e.g., anti-reflective films) to each other; and a touch panel unit formed on the functional film. The touch panel unit includes: a first adhesive film; a first transparent electrode film stacked on the first adhesive film; a second adhesive film; and a second transparent electrode film. An electrode and a coating layer of the electrode are formed on the second transparent electrode film, and a third adhesive film and a window glass are sequentially stacked on the coating layer. The air gap may be removed during lamination.

[0190] Hereinafter, the present invention will be described in more detail with reference to some examples. It should be understood that these examples are provided for illustration only and should not be interpreted as limiting the present invention in any way.

[0191] For clarity, descriptions of details clear to one skilled in the art will be omitted.

[0192] Examples

[0193] (A) Monomer mixture

[0194] (a1) 2-ethylhexyl acrylate (EHA) was used.

[0195] (a2) 4-hydroxybutyl acrylate (HBA) was used.

[0196] (B) Organic particles

[0197] (b1) organic particles having a core-shell structure consisting of a polybutyl acrylate (PBA) core and a polymethyl methacrylate (PMMA) shell, containing 40 wt % of the shell, and having an average particle size of 230 nm and a refractive index (N B ).

[0198] (b2) organic particles having a core-shell structure consisting of a polybutyl acrylate (PBA) core and a polymethyl methacrylate (PMMA) shell, containing 30 wt% of the shell, and having an average particle diameter of 230 nm and a refractive index (N B ).

[0199] (b3) organic particles having a core-shell structure consisting of a polybutyl acrylate (PBA) core and a polymethyl methacrylate (PMMA) shell, containing 30 wt % of the shell, and having an average particle diameter of 130 nm and a refractive index (N B ).

[0200] (b4) organic particles having a core-shell structure consisting of a poly(2-ethylhexyl acrylate) (PEHA) core and a polymethyl methacrylate (PMMA) shell, containing 30 wt% of the shell, and having an average particle diameter of 140 nm and a refractive index (N) of 1.48 were used. B ).

[0201] (C) Initiator

[0202] (c1) Incarnate 651 (2,2-dimethoxy-2-phenylacetophenone, BASF Co., Ltd.) was used as a free radical photopolymerization initiator.

[0203] (c2) Incarnate 184 (1-hydroxycyclohexyl phenyl ketone, BASF) was used as a free radical photopolymerization initiator.

[0204] (c3) Azobisisobutyronitrile (AIBN, Junsei Co., Ltd.) was used as a thermal polymerization initiator.

[0205] Example 1

[0206] In a glass container, 4 parts by weight of (b1) organic particles and 0.005 parts by weight of (c1) photopolymerization initiator (Vincasol 651) were fully mixed with 100 parts by weight of a monomer mixture containing 70% by weight of (a1) 2-ethylhexyl acrylate and 30% by weight of (a2) 4-hydroxybutyl acrylate. The dissolved oxygen in the glass container was purged with nitrogen, and then the mixture was polymerized by irradiating with ultraviolet light for several minutes using a low-pressure lamp (BL lamp, Samkyo Co., Ltd.), thereby obtaining a 1,000 cp viscosity and a refractive index (N) as listed in Table 1. AB ) 0.35 parts by weight of (c2) a photopolymerization initiator (Yanjiagu 184) was further added to the produced hydroxyl-containing (meth)acrylic copolymer to prepare an adhesive composition.

[0207] The prepared adhesive composition was coated on a polyester film (release film, polyethylene terephthalate film, thickness: 50 μm) to form an adhesive film of 100 μm thickness. The upper side of the adhesive film was covered with a 75 μm thick release film, and then both surfaces of the adhesive film were irradiated with light for 6 minutes using a low-pressure lamp (BL lamp, Sankyo Co., Ltd.), thereby obtaining a transparent adhesive sheet.

[0208] Examples 2 to 7 and Comparative Example 1

[0209] A transparent adhesive sheet was manufactured in the same manner as in Example 1, except that the amount of each of the components in Example 1 was modified as listed in Table 1.

[0210] Example 8

[0211] Based on 100 parts by weight of a mixture containing 80% by weight of (a1) 2-ethylhexyl acrylate and 20% by weight of (a2) 4-hydroxybutyl acrylate, 4 parts by weight of (b3) organic particles and 0.05 parts by weight of (c3) thermal polymerization initiator (AIBN, Purely) were introduced into a glass container, and then 130 parts by weight of ethyl acetate were introduced into the glass container based on 100 parts by weight of the (A) + (b3) mixture. Next, the components were mixed thoroughly. The dissolved oxygen in the glass container was purged with nitrogen, and then a typical solution polymerization was carried out at 65° C., thereby obtaining a glass having a refractive index (N) as listed in Table 1. AB ) 0.35 parts by weight of (c2) a photopolymerization initiator (Yanjiagu 184) was further added to the produced hydroxyl-containing (meth)acrylic copolymer to prepare an adhesive composition.

[0212] Next, a transparent adhesive sheet was produced in the same manner as in Example 1, and was further subjected to hot air drying at 80° C. for 20 minutes and at 100° C. for 5 minutes.

[0213] The properties of the transparent adhesive sheets prepared in the Examples and Comparative Examples listed in Table 1 were evaluated.

[0214] Evaluation characteristics

[0215] (1) Storage modulus: The viscoelasticity was measured under automatic strain conditions at a strain of 1% and a shear rate of 1 radian / second using a dynamic viscoelasticity instrument ARES (MCR-501, Anton Paar Co., Ltd.). After removing the release film, the adhesive film was stacked to a thickness of 500 μm. Next, the stack was punched using an 8 mm diameter punch to prepare a sample. The storage modulus of the sample was measured at a heating rate of 5°C / min at a temperature of -60°C to 90°C using an 8 mm fixture, and the storage modulus at each of -20°C, 25°C, and 80°C was recorded.

[0216] (2) Average slope: The temperature-dependent storage modulus distribution of the adhesive film is plotted in a graph, where the x-axis represents temperature (°C) and the y-axis represents storage modulus (kPa). The average slope within -20°C to 80°C is calculated by Equation 1:

[0217] [Equation 1]

[0218] Average slope=(Mo(80℃)-Mo(-20℃)) / (80-(-20))

[0219] (wherein Mo(80°C) is the storage modulus at 80°C, and Mo(-20°C) is the storage modulus at 20°C).

[0220] (3) T-peel strength of non-corona PET film: A PET film having a size of 150 mm×25 mm×75 μm (length×width×thickness), and an adhesive film sample having a size of 100 mm×25 mm×100 μm (length×width×thickness) were obtained from each of the adhesive sheets of the examples and comparative examples. The PET film 310 was laminated to both surfaces of the adhesive film 300 sample, thereby preparing a sample as shown in FIG2(a). The sample was autoclaved at 50°C for 1,000 seconds at a pressure of 3.5 bar and fixed to a TA.XT_Plus texture analyzer (Stable Microsystems). Referring to FIG2(b), one side of the PET film 310 was kept fixed and the other side of the PET film 310 was pulled at a rate of 50 mm / min at 25°C using the TA.XT_Plus texture analyzer, thereby measuring the T-peel strength at 25°C (see FIG2(b)).

[0221] In addition, one side of the PET film 310 was kept fixed and the other side of the PET film 310 was pulled at a rate of 50 mm / min at 60° C. using a TA.XT_Plus texture analyzer, thereby measuring T-peel strength at 60° C.

[0222] (4) T-peel strength of corona-treated PET film: A PET film having a size of 150 mm×25 mm×75 μm (length×width×thickness) was subjected to corona treatment twice (total dose: 156) using a corona treatment device under a corona discharge of a dose of 78. An adhesive film sample having a size of 100 mm×25 mm×100 μm (length×width×thickness) was obtained from each of the adhesive sheets of the examples and comparative examples. The corona-treated surface of the PET film 310 was laminated to both surfaces of the adhesive film 300 sample, thereby preparing a sample as shown in FIG. 2( a). The sample was autoclaved at a pressure of 3.5 bar at 50° C. for 1,000 seconds and fixed to a TA.XT_Plus texture analyzer (Stable Microsystems). 2( b ), one side of the PET film 310 was kept fixed and the other side of the PET film 310 was pulled at a rate of 50 mm / min at 25° C. using a TA.XT_Plus texture analyzer, thereby measuring the T peel strength at 25° C. (see FIG. 2( b )).

[0223] In addition, one side of the PET film 310 was kept fixed and the other side of the PET film 310 was pulled at a rate of 50 mm / min at 60° C. using a TA.XT_Plus texture analyzer, thereby measuring T-peel strength at 60° C.

[0224] (5) Turbidity: Using a turbidity meter (NDH 5000, Nippon Denshoku Co., Ltd.), the turbidity of a sample having a thickness of 100 μm was measured according to American Society for Testing and Measurement (ASTM) D1003-95 (Standard Test for Turbidity and Light Transmittance of Transparent Plastics).

[0225] (6) Haze after 200% stretching: Both ends of a sample of the manufactured adhesive film (5 cm×5 cm, thickness: 100 μm) were fixed to both sides of a horizontal tensile tester, and then the release films were removed from both surfaces of the sample. After the sample was subjected to 200% stretching in the longitudinal direction (the length reached was twice its initial length, that is, a length of 10 cm), a glass plate was placed on the lower side of the sample and a release film was placed on the upper side of the sample, and then the sample was bonded to the glass plate by a 2 kg roller, thereby preparing a stretched sample. Next, the release film was removed from the upper side, and then the haze of the sample having a thickness of 100 μm was measured in the same manner as described above.

[0226] (7) Recovery rate: The recovery rate was measured by the following procedure. When both ends of each polyethylene terephthalate (PET) film 310 (thickness: 75 μm) having a size of 50 mm×20 mm (length×width) were defined as a first end and a second end, respectively, a sample was prepared as follows: via each of the adhesive films 300 prepared in the example and the comparative example and having a size of 20 mm×20 mm (length×width), the ends of the two PET films 310 were bonded to each other in the order of first end of the first PET film 310 / adhesive film 300 / second end of the second PET film 310, and the contact area (adhesive film bonding portion 302) between each PET film 310 and the adhesive film 300 was 20 mm×about 20 mm (length×width) (see FIGS. 3(a) and 3(b)). Referring to FIG. 3( a ), at room temperature (25° C.), the clamps were fixed to the non-adhesive ends (clamp fixing portions 312) of the PET film 310 of the sample, respectively. Next, the clamps on one side were kept fixed, and the clamps on the other side were pulled at a rate of 300 mm / min to a length of 1,000% of the thickness (unit: micrometer) of the adhesive film 300 (the initial thickness (X 0 ) and then maintained for 10 seconds. Next, if a force of 0 kPa is applied to the adhesive film by restoring the adhesive film 300 at the same rate as the pulling rate (about 300 mm / min), the increased length of the adhesive film 300 is defined as X f (Unit: micrometer), then the recovery rate (%) is calculated by Equation 3.

[0227] [Equation 3]

[0228] Recovery rate (%) = (1-(X f / X 0 ))×100

[0229] (8) Bubble generation area (%): An adhesive (length×width×thickness: 13 cm×about 3 cm×about 100 μm) comprising a 50 μm thick PET film stacked on one surface and a 100 μm thick PET film stacked on the other surface was folded in half toward the 50 μm thick PET film so that the length of the adhesive film was halved, and then placed between parallel frames with a gap of 1 cm. Next, the adhesive film was subjected to aging at 70° C. and 93% RH for 24 hours, and then the image was analyzed using Mac-View software (Mo Teng Co.) to measure the ratio of the area occupied by bubbles to the area of ​​the adhesive film, the image being obtained by observing the adhesive film portion subjected to bubbles using an optical microscope (EX-51, Olympus Corporation, magnification: 30 times).

[0230] Table 1

[0231]

[0232] In Table 1, the amounts of (a1) and (a2) in the monomer mixture ((a1) + (a2)) are given in % by weight, and the amounts of (B) and (C) are given in parts by weight based on 100 parts by weight of the monomer mixture. AB -N B | represents the difference in refractive index between the organic particles and the hydroxyl-containing (meth)acrylic copolymer. The refractive index is rounded to three decimal places.

[0233] As shown in Table 1, it can be seen that the adhesive films containing organic particles of Examples 1 to 8 have a storage modulus that allows the adhesive film to maintain viscoelasticity in a wide temperature range and exhibit viscoelasticity in a similar wide temperature range, which is due to the small average slope of the storage modulus in the range of -20°C to 80°C. In addition, it can be seen that the adhesive films of Examples 1 to 8 exhibit characteristics such as low turbidity (transmittance) and excellent adhesion, as well as excellent recovery rate, bubble generation area (%) in a high temperature and high humidity environment, etc.

[0234] On the other hand, the adhesive film of Comparative Example 1 not including organic particles exhibited deterioration of adhesive force and storage modulus at high temperatures and deterioration of recovery rate and bubble generation region, compared to the adhesive film of the present invention.

[0235] Although the present invention has been described with reference to some embodiments, it should be understood that the aforementioned embodiments are provided for illustration only and should not be construed as limiting the present invention in any way, and that various modifications, changes, alterations and equivalent embodiments may be made by those skilled in the art without departing from the spirit and scope of the present invention.

[0236] Embodiments of the present invention have been disclosed herein, and although specific terms are used, such terms are used and interpreted only in a general and descriptive sense, and not for limiting purposes. In some cases, it will be clear to those skilled in the art from the time of filing this application that, unless otherwise specifically noted, the features, characteristics, and / or elements described in conjunction with a specific embodiment may be used alone or in combination with the features, characteristics, and / or elements described in conjunction with other embodiments. Therefore, it should be understood by those skilled in the art that various changes may be made to form and detail without departing from the spirit and scope of the invention as set forth in the claims.

Claims

1. A (meth)acrylic pressure-sensitive adhesive film having an average slope of -9.9 to 0, measured in a storage modulus versus temperature plot in the range of -20°C to 80°C, wherein the x-axis represents temperature and the y-axis represents storage modulus, The (meth)acrylic pressure-sensitive adhesive film has a storage modulus at -20°C of 10 kPa to 1,000 kPa, The (meth)acrylic pressure-sensitive adhesive film has a storage modulus at 25° C. of 10 kPa to 90 kPa, The (meth)acrylic pressure-sensitive adhesive film is formed of an adhesive composition, the adhesive composition comprising a monomer mixture forming a (meth)acrylic copolymer, the monomer mixture comprising a comonomer, a homopolymer of the comonomer having a glass transition temperature of -150°C to 0°C and the comonomer being selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate and lauryl (meth)acrylate, The (meth)acrylic copolymer has a glass transition temperature of -150°C to -13°C. 2 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has a storage modulus at −20° C. of 10 kPa to 500 kPa. 3 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has a storage modulus at −20° C. of 20 kPa to 200 kPa. 4 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has a storage modulus at −20° C. of 50 kPa to 200 kPa. 5 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has a storage modulus at 80° C. of 10 kPa to 1,000 kPa. 6 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has a storage modulus at 80° C. of 10 kPa to 500 kPa. 7 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has a storage modulus at 80° C. of 10 kPa to 100 kPa. 8 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has a storage modulus at 80° C. of 10 kPa to 30 kPa. 9 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has an average slope of −6 to 0. 10 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has an average slope of −5 to 0. 11 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has an average slope of −4 to 0. 12 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has an average slope of −3 to 0. 13 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has an average slope of −1.2 to 0. 14 . 14 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has an average slope of −1.0 to 0. 15 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has an average slope of −0.5 to 0. 16 . The (meth)acrylic pressure-sensitive adhesive film of claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has a T-peel strength of 400 to 4,000 gf / inch measured at 25° C. with respect to a corona-treated polyethylene terephthalate film. 17 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film has a T-peel strength of 200 to 2,000 gf / inch measured at 60° C. with respect to a corona-treated polyethylene terephthalate film. 18 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the monomer mixture further comprises a hydroxyl-containing (meth)acrylate. 19 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the adhesive composition further comprises organic particles. 20 . The (meth)acrylic pressure-sensitive adhesive film according to claim 19 , wherein the organic particles have an average particle diameter of 10 nm to 400 nm. 21 . The (meth)acrylic pressure-sensitive adhesive film of claim 19 , wherein the organic particles are present in an amount of 0.1 parts by weight to 15 parts by weight based on 100 parts by weight of the monomer mixture forming the (meth)acrylic copolymer. 22 . The (meth)acrylic pressure-sensitive adhesive film of claim 19 , wherein a difference in refractive index between the organic particles and the monomer mixture is 0.5 or less.

23. The (meth)acrylic pressure-sensitive adhesive film according to claim 18, wherein the monomer mixture comprises 5 to 40 wt% of the hydroxyl-containing (meth)acrylate monomer and 60 to 95 wt% of the comonomer, based on the total amount of the monomer mixture. 24 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the monomer mixture further comprises a carboxyl group-containing monomer. 25 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the adhesive composition further comprises at least one of an initiator and a cross-linking agent. 26 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the adhesive composition further comprises a silane coupling agent. 27 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film having a thickness of 100 μm has a haze of 5% or less.

28. The (meth)acrylic pressure-sensitive adhesive film according to claim 1, wherein the (meth)acrylic pressure-sensitive adhesive film having a thickness of 100 μm has a haze of 5% or less as measured after the (meth)acrylic pressure-sensitive adhesive film is subjected to 200% stretching.

29. The (meth)acrylic pressure-sensitive adhesive film according to claim 1, wherein the (meth)acrylic pressure-sensitive adhesive film having a thickness of 100 μm has a recovery rate of 30% to 98%, which is represented by Equation 3: Equation 3 Recovery rate (%) = (1-(X f / X0))×100 Wherein X0 is the initial thickness of the (meth)acrylic pressure-sensitive adhesive film, and X f is the length of the (meth)acrylic pressure-sensitive adhesive film increased after a test piece including a first end of a first polyethylene terephthalate film attached to the (meth)acrylic pressure-sensitive adhesive film, a second end of the (meth)acrylic pressure-sensitive adhesive film attached to a second polyethylene terephthalate film is pulled at a rate of 300 mm / min to a length 10 times the initial thickness of the (meth)acrylic pressure-sensitive adhesive film, maintained at that position for 10 seconds, and then recovered at the same rate as the stretching rate, followed by applying a force of 0 kPa to the (meth)acrylic pressure-sensitive adhesive film.

30. The (meth)acrylic pressure-sensitive adhesive film according to claim 1, wherein the (meth)acrylic pressure-sensitive adhesive film has a bubble generation area of ​​0%, as measured by folding a (meth)acrylic pressure-sensitive adhesive film sample comprising a first polyethylene terephthalate film having a thickness of 50 μm stacked on one surface of the (meth)acrylic pressure-sensitive adhesive film and a second polyethylene terephthalate film having a thickness of 100 μm stacked on a second surface of the (meth)acrylic pressure-sensitive adhesive film in half, then placing the (meth)acrylic pressure-sensitive adhesive film sample between parallel frames having a gap of 1 cm, and then subjecting the (meth)acrylic pressure-sensitive adhesive film sample to aging for 24 hours at 70° C. and 93% RH. 31 . The (meth)acrylic pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic pressure-sensitive adhesive film is an adhesive film cured by ultraviolet light irradiation.

32. A display component comprising: Optical films; as well as The (meth)acrylic pressure-sensitive adhesive film according to claim 1, which is attached to one or both surfaces of the optical film.

Citation Information

Patent Citations

  • Acrylic pressure sensitive adhesive compositions

    KR1020070055363A

  • Adhesive film for polarizing plate, adhesive composition for the same, polarizing plate comprising the same, and optical display apparatus comprising the same

    CN103865411A

  • Acrylic pressure-sensitive adhesive composition for polarizing film

    CN1764679A